APLIKASI DARING BERBASIS ANDROID FISH SMART SEBAGAI SOLUSI CERDAS UNTUK MENINGKATKAN MENINGKATAN PEREKONOMIAN WILAYAH MARITIM INDONESIA SECARA BERKELANJUTAN: ANDROID BASED ONLINE APPLICATION FISH SMART AS A INTELLIGENT SOLUTION TO IMPROVE COASTAL FISHERMAN QUALITY TO INDONESIA'S MARITIME ECONOMY IN A SUSTAINABLE MANNER - Muhammad Bayu Purnama; Deny Nusyirwan; Desi Oktavia; Gilang Satria Wahyu Dewantara (Jurnal Teknologi dan Terapan Bisnis, 2020)
Fishermen poverty is a problem that must be overcome, as well as difficulties in improving the welfare of fishermen in coastal areas due to internal weaknesses and the influence of external factors. Fishermen do not feel the limited education or opportunities to access and master technology. This factor is due to not having sufficient capital, such as the condition of the fishermen's economic difficulties. On the other hand, external factors are increasingly intense competition, market mechanisms and the bargaining position of fishermen to sell fish they have caught. FISH SMART is an daring trading application based on android, and acts as a capital market broker for fish products. The way it works is by interacting directly through a communication system between fishermen and consumers. This application system is easy to operate so that fishermen will be able to offer fish prices according to quality. Through this interaction and cooperation, sustainability will be established as a booster for the fishermen's economy and educate fishermen on the mastery of technology. In the end, it will improve Indonesia's maritime economy in a sustainable manner.